Unifying Themes in Complex Systems Proceedings of the Fifth International Conference on Complex Systems - Minai, Ali A.; Braha, Dan.; Bar-Yam, Yaneer; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
The International Conference on Complex Systems (ICCS) creates a unique atmosphere for scientists of all fields, engineers, physicians, executives, and a host of other professionals to explore common themes and applications of complex system science. With this new volume, Unifying Themes in Complex Systems continues to build common ground between the wide-ranging domains of complex system science.
Introduction -- Organization -- Conference Programme -- A Simple Approach to Multi-Predator Multi-Rey Pursuit Domain -- Simulated Niche Partitioning by Bacteria -- Predictive Modeling for Fisheries Management in the Colombian Amazon -- Complexity and Diversity of Digraphs -- Complex Knowledge Networks and Invention Collaboration -- Random Evolution of Idiotypic Networks and Invention Collaboration -- Random Evolution of Idiotypic Netwworks: Dynamics and Architecture -- Constructing Scale-Free Networks by a Matrix Stability Approach -- Fractal Patterns of Medeled Zoning Patterns in Calcite -- Complexity and Army Transformation -- A Model of Biological Attacks on a Realistic Population -- Cartography Applications for Autonomous Sensory Agents -- Dissipation and Statistical Mechanics of Granular Gas -- The Nash Equlilibrium Revistited -- Adaption and Coevolution on an Emergent Global Competitive Landscape -- Complex Dynamics of the Cardiac Rhythms -- The Ecological Ideal Free Distribution and Distributed Networked Control Systems -- Protocol Requirements for Self-Organizing Artifacts: Towards an Ambient Intelligence -- Modeling Social Structure as Networks Effects: Rewards for Learning Improve Performance -- Permeable Boundaries in Organizational Learning -- Mobility of Innovators and Prosperity of Geographical Technology Clusters -- Towards Computing the Battle for Hearts and Minds: Lessons from the Vendée -- The Structure of Algal Population in the Presence of Toxicants -- Vortex Analogue of Molecules -- Handling Resource Oscillations Through Selective Misinformation -- On the Evolution of Structure in Ecological Networks -- Spatio-temporal Dynamics in a Turing Model -- Evolution of Money Distribution in a Simple Economic Model -- Chaos as a Bridge Between Determinism and Probaliblity in Quantum Mechanics -- The Use of Fractal Dimension Calculation Algorithm to Determine the Nature of Autobiographical Memories Distribution across the Life Span.-An Formally Exact Solution for a Time-Dependent Quantum System -- Human-technology Integration -- Crafting a Social Context for Medical Informatics Networks -- Modeling Safety Outcomes on Patient Care Units -- Defining Emergent Descriptions by Information Preservation. - Universality Classes of Complexity -- Anti-Resonance in Complex Systems -- Networks of Genetic Loci and the Scientific Literature -- A Multi-Modeling Approach to the Study of Animla Behaviour -- Patterns of Negotioation: A New Way of Looking at Martketplace B2B Negotiations -- Organized All the Way Down: The Local Complexity of "Thick" Social Systems" -- Comparing the Dynamics of Stomatal Networks to the Problem-Solving Dynamics of Cellular Computers -- A New Approach to Ecological Risk Assessment: Simulating effects of Global Warming on Complex Ecological Networks.
Keywords: Physics; Artificial intelligence; Engineering; Physics; Statistical Physics, Dynamical Systems and Complexity; Complexity; Artificial Intelligence (incl. Robotics).